Vascular Endothelial Growth Factor 936 C/T Gene Polymorphism in Indonesian Subjects with Diabetic Polyneuropathy - Barus, Jimmy (Open Access Maced J Med Sci, 2018)
AIM: This study aimed to confirm the role of f VEGF gene 936 C/T polymorphism and Diabetic Polyneuropathy (DPN) in the Indonesian population as well as to investigate its relationship with VEGF-A level and the role of vascular risk factors. MATERIAL AND METHODS: This was a cross-sectional study involving 152 subjects. Clinical symptoms and signs of DPN were examined using DNE and DNS scoring followed by nerve conduction study. All subjects underwent anthropometric, clinical examination and laboratory procedures to obtain body mass index, HbA1C level, lipid profile, Polymorphism of +936 C/T VEGF gene (PCR-RFLP technique), and VEGF-A plasma level (ELISA). Statistical analysis using a t-test or Mann-Whitney was performed to assess continuous data and Chi-square for categorical data. Multivariate logistic regressions were also performed to determine the relationship between independent variables and DPN. RESULTS: Sixty-nine (45.4%) fulfilled the diagnostic criteria of DPN. There was a significant association between CT + TT genotype and DPN (OR 0.35 95%CI 0.16-0.79 p = 0.01). Multivariate logistic regression showed that plasma VEGF-A level (OR = 1.003; 95% CI = 1.000-1.007; p = 0.03), diabetes duration (OR = 1.108; 95% CI = 1.045-1.175; p = 0.001), and CT+TT genotype (OR = 0.347; 95%CI = 0.148-0.817; p = 0.013) were associated with DPN. Sub-group analysis on subjects with HbA1C level ≥7% showed that VEGF-A (OR = 1.011; 95%CI = (1.004-1.017; p = 0.03), diabetes duration (OR = 1.245; 95% CI = 1.117-1.388; p < 0.001), CT + TT genotype (OR = 0.259; 95%CI = 0.074-0.911p = 0.035), with an adition of HDL (OR = 0.916; 95% CI = 0.857-0.978; p = 0.009) were significant predictors of DPN while LDL (OR = 1.017; 95% CI = 1.000-1.035; p = 0.053) acted as modifying factor. CONCLUSION: It appeared that CT + TT genotype of VEGF +936 gene might act as a protecting factor for DPN while VEGF-A, diabetes duration, HDL, and LDL acted as risk factors especially on subjects with HbA1C level ≥ 7.